Bovine herpes mammillitis (Gulwaddee) – a less known disease of cows and buffaloes in Pakistan - Firyal, Sehrish; Ali, Muhammad Muddassir; Muhammad, Ghulam; Saqib, Muhammad; Rashid, Immad; Tahir, Muhammad Zeeshan; Awan, Ali Raza; Wasim, Muhammad; Tayyab, Muhammad (Buffalo Bulletin, 2019)
Bovine herpes mammillitis is a disease of cows and buffaloes associated with bovine herpes mammillitis virus 2 and characterized clinically by successive appearance of plaques, vesicles ulcers and scabs on teats and udder. Vesicle formation, a characteristic feature of early stages of the disease in cow is either absent or occurs rarely in dairy buffaloes. The disease is worldwide in distribution but has not been reported from Pakistan. This is despite the fact that one clinical form of the disease (colloquially known as Gulwaddee in Punjabi) has been observed by most of the seasoned Pakistani veterinary practitioners. Most cows and buffaloes are affected by latent and sub-clinical form of the disease and only a few infected animals develop its clinical form. Stress of calving, udder edema and hormonal changes close to calving are important predisposing factors. The condition is usually sporadic although outbreaks have also been documented. It is more prevalent in cows and buffaloes in their first lactation. The causative virus multiplies at a temperature lower than the temperature of the rest of the body. Therapeutic interventions that can be used for the treatment of bovine herpes mammillits include debridement of the scab covered lesion, topical and parenteral administration of antibiotics, topical administration of lysine/propolis, topical and oral administration of acyclovir (an anti-herpes virus drug), oral administration of zinc sulphate and other immunity enhancing agents and parenteral administration of antihistamine and anti-infammatory drugs. Therapeutic interventions proposed for future research include investigation of the oral use of zinc sulphate, local infiltration of acyclovir into the lesions and use of infrared lamp to increase the temperature of the lesion. No vaccine is currently available recommended control and prevention measures include biosecurity, prevention and proper treatment of udder edema, insect control and milking time hygiene.